Ethnographic Study of a Single Teacher School in Kerala - Praveen G., Manoj; Safwan C.P., Muhammed (JOURNAL OF INDIAN EDUCATION, 2015)
A single teacher school or Multi-grade Learning Centre (MGLC) occurs in primary education when a teacher has to teach two or more primary school student grades in the same class. MGLC plays an active role in giving primary education to marginalised society. MGLC schools clearly keep their motto “if the child cannot reach the school, take the school to the child”. Here, the teacher creates a home atmosphere, so students are fearless and treat the school as a place like their ‘kudi’ (home). Apart from being a school, MGLC becomes a part of entire village activities. All needs of the village, be it social, cultural or health related matters are fulfilled by MGLC. The teacher demands direct involvement of every student in class activities. Here, traditional teaching methods like lecture method, etc. are not effective since, at a time, students belonging to four grades are involved in learning activities. In spite of the sincere efforts of the teacher, the study reveals that the students of MGLC have low aspirations and achievement levels and are bound by their social and cultural settings.